PLIOCENE CORAL DIVERSITY OF THE TOGOPI FORMATION IN THE DENT PENINSULA, SABAH: IMPLICATIONS FOR THE DEVELOPMENT OF THE INDO-PACIFIC CENTRE OF DIVERSITY - VARN MAY, JASMIN SAW (2019)
The Sulu Sea is part of the biodiversity hotspot in the Malay Archipelago. The palaeobiological history of the region remains poorly documented despite its significance for present-day global biodiversity as the focus of the modern global marine biodiversity hotspot.